The colostomy impact score: development and validation of a patient reported outcome measure for rectal cancer patients with a permanent colostomy. A population‐based study. (January 2017) - Thyø, A.; Emmertsen, K. J.; Pinkney, T. D.; Christensen, P.; Laurberg, S.
Abstract: Aim: The aim was to develop and validate a simple scoring system evaluating the impact of colostomy dysfunction on quality of life (QOL) in patients with a permanent stoma after rectal cancer treatment. Method: In this population‐based study, 610 patients with a permanent colostomy after previous rectal cancer treatment during the period 2001–2007 completed two questionnaires: (i) the basic stoma questionnaire consisting of 22 items about stoma function with one anchor question addressing the overall stoma impact on QOL and (ii) the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ) C30. Answers from half of the cohort were used to develop the score and subsequently validated on the remaining half. Logistic regression analyses identified and selected items for the score and multivariate analysis established the score value allocated to each item. Results: The colostomy impact score includes seven items with a total range from 0 to 38 points. A score of ≥ 10 indicates major colostomy impact (Major CI). The score has a sensitivity of 85.7% for detecting patients with significant stoma impact on QOL. Using the EORTC QLQ scales, patients with Major CI experienced significant impairment in their QOL compared to the Minor CI group. Conclusion: This new scoring system appears valid for the assessment of the impact on QOL from having a permanent colostomy in a Danish rectal cancer population. It requires validation in non‐Danish populations prior to its acceptance as a valuable patient‐reported outcome measure for patients internationally.